DETERMINANTS OF PROFITABILITY OF GENERAL INSURANCE COMPANIES IN INDONESIA - Faisal Azmi; Tony Irawan; Hendro Sasongko (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
This paper investigates the determinants of profitability of General Insurance in Indonesia, focusing on firm-specific factors and macroeconomics factors. General Insurance in Indonesia play important role in the economy by providing protection of risk of loss either to organizations and individuals. Based on this background, the aim of this paper is to study and improve the profitability of general insurance through a random effect analysis of 40 general insurance companies since 2013 until 2017. The data obtained is time series data and cross section data so that the data analysis in this study uses Panel Data Regression Analysis. The empirical study shows that firm size, liquidity ratio, equity growth, underwriting result, return on investment, input cost, claim ratio, technical ratio, economic growth rates and Bank Indonesia interest rate are significant factors that affect profitability of general insurance companies. Companies can improve their profitability by planning, monitoring and defining financial strategy based on the relation whether – positive or negative, between significant factors and profitability.